Paradigma Penilaian Pembelajaran PAI pada Kurikulum KTSP dan Kurikulum Merdeka untuk Tingkat SMP - Shodikun, Shodikun; Muslih, Moh.; Soebari, Titien Soewastiningsih (Absorbent Mind, 2024)
This research examines the Islamic Religious Education (PAI) learning assessment paradigm in the Education Unit Level Curriculum (KTSP) and the Merdeka Curriculum at the Junior High School (SMP) level. The main purpose of this assessment is to measure the achievement of learning objectives, assess the effectiveness of teaching, and evaluate the suitability between the learning approach and the curriculum used. The move from the KTSP Curriculum to the Independent Curriculum often creates challenges, especially for schools that have not yet gone through the 2013 Curriculum (K-13). The KTSP curriculum uses traditional assessment methods such as written exams and formative tests, while the Merdeka Curriculum emphasizes a holistic approach that includes cognitive, affective, and psychomotor aspects. This research identified three main aspects that were evaluated: achievement of learning objectives, teaching effectiveness, and suitability of learning approaches to the curriculum. The assessment instruments used include written tests, class observations, questionnaires, and student portfolios. The assessment stages include planning, implementation, data analysis, decision making, feedback, follow-up, and ongoing monitoring and evaluation. Through a comprehensive and continuous assessment approach, it is hoped that the quality of PAI learning in junior high schools can be improved in line with the demands of the times and students' needs.